Arabic Metaphor Management As a Kyai Sholeh Islamic Dakwah Model on Tolerance and Social Harmony - Irhamni -; Khoirul Adib (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research aims at describing the Arabic metaphor management as a Kyai Sholeh Islamic dakwah model on tolerance and social harmony. To fulfill the target, researcher uses the descriptivequalitative research method that is carried out in natural background and uses phenomenological approach because the research attempts to understand the phenomena that occur in research subjects. The results shaw that the practice of the tolerance model and ukhuwah among Moslems developed by Kyai Sholeh is syari’at and tasawuf ethic laws as its base model. According to the meaning of the tolerance and ukhuwah as the flexible and elaborative stand, thus the fiqh law that is developed is law with its variety offering alternatives with consideration of ummats’ capacity as reflected in galak gampil law (the hardest law and the softest law). The Arabic metaphors used by Kyai Sholeh are ÑãÖÇä (Ngawu) ” becoming ash”, ãÊÈÍÑ(nyegoro) ”like sea”, ÓãÇÁ(langit) ”sky”, ÃÑÖ(bumi) ”earth”, ãØÑ(udan) ”rain”, Íãá(nggendong) ”carrying someone or something on back”, ÌæÒÉ(mur) ”nut”, ÔÏÉ- ãÑæäÉ(galak gampil) ”hard-soft”, Ïáíá(dalil) ”proposition”, ÈäÏæÞíÉand (bedil) ”gun.”Keywords: Arabic metaphor, Kyai Sholeh, Islamic dakwah model, tolerance and social harmony.